(untitled) (Eurasian Journal of Philology Science and Education, 2025)
This article develops a methodology for analyzing the literary mastery of A.P. Chekhov in class at a higher educational institution. The purpose of the article is to develop effective methods and techniques for analyzing the literary mastery of the great writer in university audience. The main direction of the scientific research carried out is the methodology for analyzing an epic literary work based on active and interactive teaching methods. The idea of scientific research is that a comparative analysis of a writer’s early and later works leads students to a deep understanding of the nature of his literary skills. The scientific significance of the work is characterized by the fact of its theoretical conclusions and results can serve to find effective ways to analyze literary works based on a comparison of their artistic form and issues. This approach makes it possible to see the development of the writer’s literary skills. The practical significance of the article lies in the fact that the method proposed in it for analyzing the literary mastery of A.P. Chekhov can be used to conduct practical classes on the study of epic works in higher education. The research is interdisciplinary in nature, since it was carried out using tools, conclusions and provisions of literary criticism, pedagogy, didactics and methods of teaching literature. The practical significance of the research results is expressed in the fact that the article describes the methodology for analyzing literary mastery based on the use of innovative teaching methods. This methodology may be of interest for the development of effective technologies for studying works of prose in higher education. Keywords: literary innovation, literary skill, methodology for analyzing a story, interactive learning, A.P. Chekhov.